Representation and discourse: an analysis of the representation of the female figure in art - Rublescki, Anelise (2019)
This article aims to reflect on the feminine archetypes in the visual arts, through the imagistic analysis of some canons of Western painting. The following issues are discussed throughout the text such as the construction of the idealization of the female body, gender relations and power. This reflection was based on the theories of the representation of the sociologist Stuart Hall (1997) and the study of the discourse theories and the subjects of the language proposed by the linguist Patrick Charaudeau, who can identify the discourse produced by the images. We conclude that the analyzed images are not neutral of meanings and were produced with certain intentionalities.